Guerrilla gardening or informal planting in Quezon City: Feasibility study - Anunciado, Ma. Shiela; Kimayong, Doreen; Del Rio, Susan; Schreinemachers, Pepijn; Perez, Cristina; Bonifacio, Pocholo (CGIAR System Organization, 2025)
This feasibility study examines guerrilla gardening or informal planting as a community-led urban greening and food security strategy in Quezon City. Using a mixed-methods approach including surveys with 54 respondents across 18 barangays, 18 key informant interviews with barangay officials, and field observations. The study assessed the social, environmental, and policy feasibility of informal gardening in underutilized public and private spaces. Results show that informal gardening is widespread, socially accepted, and primarily driven by food security and economic needs, particularly among women, older adults, and long-term residents. The practice generates multiple benefits, including improved access to fresh food, cleaner and greener neighborhoods, stronger social cohesion, and positive mental well-being. While public and barangay-level support is strong, informal gardening faces practical constraints such as limited tools, technical knowledge, soil quality issues, and policy ambiguity, as existing urban agriculture policies focus mainly on formal, registered farms. The study concludes that guerrilla gardening is a feasible and effective complement to formal urban greening programs. With targeted resource support and enabling local policies, informal planting can contribute meaningfully to urban food security, environmental sustainability, and community resilience.